Sobre graça, dignidade e beleza em Friedrich Schiller e Heinrich von Kleist - Silva, Carina Zanelato [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study has the objective to discuss the theories of Friedrich Schiller (1759-1805) and Heinrich von Kleist (1777-1811) about grace, dignity, beauty and sublime, comparing them in order to show the differences and the confluences of these aesthetic concepts that were developed in the classical period (with Schiller) and romantic (with Kleist).Using as a basis for the analysis of these categories the essays On Grace and Dignity (Über Anmut und Würde), by Schiller and On the Marionette Theatre (Über das Marionettentheater), by Kleist, we are showing as the aesthetic theories of the two authors reflect the tensions between Classicism and Romanticism in Germany, and how these tensions establish differences between the idea of form in Schiller and Kleist, considering that classical harmony and the dismantling of this harmony are common themes. Schiller values the maintenance of harmony and search in the art a way for men to achieve balance; Kleist, through the deconstruction of the classical model, play with form, dismantling it, turning it into a stage for the advent of the Dionysian ritual; no more serenity and harmony of Apollo that reign, but the frenzy of Dionysus, which dominates and expands in an extraordinary way. Therefore, the categories of beauty, grace and sublime acquire in Schiller and Kleist different and similar dimensions, making possible the comparison of their works. Utilizing the notes made by Friedrich Schiller about the tragedy as an instance that provides entertainment to man and freedom through moral means, we are using the plays Die Jungfrau von Orleans (Friedrich Schiller, 1801) and Penthesilea (Heinrich von Kleist, 1808) as a form of practical exemplification of how these authors used the aesthetic conceptions mentioned above for the construction of the action of his heroines, characterizing them to attend these aesthetic assumptions

O presente estudo tem como objetivo discutir as teorias de Friedrich Schiller (1759-1805) e Heinrich von Kleist (1777-1811) sobre a graça, a dignidade, o belo e o sublime, comparando-as, a fim de mostrar as divergências e as confluências dessas concepções estéticas, que foram desenvolvidas nos períodos clássico (com Schiller) e romântico (com Kleist). Tendo como referencial principal para a análise dessas categorias os ensaios Sobre graça e dignidade (Über Anmut und Würde), de Schiller, e Sobre o teatro de marionetes (Über das Marionettentheater), de Kleist, procuramos mostrar na dissertação como as teorias estéticas dos dois autores refletem as tensões existentes entre Classicismo e Romantismo na Alemanha, e como essas tensões estabelecem diferenças entre a ideia de forma em Schiller e Kleist, tendo em vista que a harmonia clássica e a desarticulação dessa harmonia são temas frequentes. Schiller preza pela manutenção da harmonia e busca na arte o caminho para que o homem alcance o equilíbrio; Kleist, pela via da desconstrução do modelo clássico, joga com a forma, de maneira a desarticulá-la, transformando-a em palco para o advento do ritual dionisíaco; não mais a serenidade e harmonia de Apolo que imperam, mas sim o frenesi de Dionísio, que domina e se expande de maneira extraordinária. Dessa maneira, as categorias do belo, da graça e do sublime ganham em Schiller e Kleist dimensões díspares e afins, abrindo espaço para a comparação de suas obras. Aproveitando-nos dos apontamentos feitos por Friedrich Schiller sobre a tragédia como instância que proporciona ao homem o entretenimento e a liberdade através de meios morais, utilizamos as peças Die Jungfrau von Orleans (Friedrich Schiller, 1801) e Penthesilea (Heinrich von Kleist, 1808) como via de exemplificação prática de como estes autores usaram as concepções estéticas apontadas acima para a construção da ação de suas heroínas...
Keywords: Schiller, Friedrich 1759-1805; Kleist, Heinrich von 1777-1811; Estética; Dignidade; Classicismo; Romantismo; Literatura; Literature